Analysis of Structural Elements to Promote Social Innovation in Panama - Alvarez Z., Marta A.; Moreno, Sidia (2019 7th International Engineering, Sciences and Technology Conference (IESTEC), 2019)
This work compares in a comparative way some advances in the promotion and management of Social Innovation adopted by four Latin American countries, including Panama, in order to generate more knowledge to promote the strengthening and design of new public policies in this ambit. Panama is in the incipient stage of Social Innovation management, compared to the other three countries analyzed: Colombia, Costa Rica and Chile. Among the structural elements addressed are: regulations, the degree of institutionality, mechanisms and incentives to promote social innovation projects and good institutionalized practices. Since 2014, Panama shows its interest and advances in the subject, in the academic and university academic sectors, which can take advantage of social innovation to obtain a greater impact in the country and promote a more inclusive social development. Colombia began efforts to promote Social Innovation in 2007, Chile and Costa Rica in 2014, as well as Panama. These three countries have a higher level of progress in the elements analyzed in their Social Innovation ecosystems than Panama, however, they do not have enough mechanisms to clearly identify the failures that prevent the strengthening of the culture of social innovation and, therefore, the establishment of much more effective public policies.
Keywords: Amérique latine; Mise en valeur; Réservé UdeM